Diagnosis and surgical treatment of nipple adenoma. Issue 6 (27th June 2014) - Wang, Chenggang; Wang, Xiao; Ma, Rong
Abstract Background Nipple adenoma is a rare and benign type of breast tumour. Because of the lack of proper understanding, it is easily overlooked and misdiagnosed by doctors. The aim of the study is to improve clinicians' awareness of the disease. Methods Evaluation of the complaints such as blood discharge or nodules on the nipple was done with physical examination, ultrasonography and cytologic evaluation (discharge cytology and curettage cytology). Resection of part of the nipple containing the tumour was performed in 11 of the 12 patients included in this study. Results Physical examination revealed nodules palpable inside the nipples in all 12 cases. However, a hypoechoic nodule was detected unilaterally inside the nipple only in three of 11 patients examined by ultrasonography. It was worth noting that six patients had cytology performed (one case on nipple discharge and five cases on curettage) and that all six had abnormal results. Cytology is often atypical or suspicious but the ultimate pathology is benign. No post‐operative recurrence was observed in any of the patients. Conclusions Physical examination and diagnostic studies are important part of the diagnostic workup, but since cytological assessment often yields atypical cells, surgical treatment and pathologic evaluation are the only approach for definitive diagnosis to rule out a potential malignancy.